Legal and institutional frameworks at national and subnational levels for biofuel promotion in Mexico - Romero Hernández, O.; Masera, O.; Romero, S.; Grunstein, M. (Center for International Forestry Research, 2011)
Mexico has recently taken significant steps toward promoting the bioenergy sector. Motivations to adopt bioenergy include: energy security, economic development and international commitments to reduce greenhouse gas emissions. These opportunities also raise concerns including the influence that expanding biofuel production may have on deforestation rates. Well-guided policies may help address this concern. This country report includes an analysis of the legal and institutional frameworks that underpin Mexico’s bioenergy sector, including provisions of policies, laws and regulations. The Mexican legal framework is well defined. The policy framework is a top-down structure with national plans at the top, linked to several sector and ministerial plans, which are finally linked to specific programmes. These programmes include strategies and subprogrammes that need to be developed in order to target feedstock, production, trade and sustainability objectives. Only a few sets of laws specifically address biofuels, and these focus on activities in the energy sector and disregard the implications for potential deforestation. Mexico has already documented priority tasks and goals, but documentation on programme details or in-depth analysis of plans, beyond simple statements, are still not fully available. Further efforts are required in the effects in agriculture and to the environment if we seek to avoid deforestation while promoting large-scale development of biofuels in Mexico. Clear provisions and integrated mechanisms that avoid environmental damage and foster the role of forestry and agriculture sectors on bioenergy have yet to be put in practice.